A Study on the Performance & Comparison of Large Cap Equity Mutual Funds in Indian Market - Aishwarya Khurana; Ankit Bhatia (Management Journal for Advanced Research, 2023)
This research project aims to study and compare the performance of large-cap equity mutual funds in the Indian market. The study is conducted over a period of five years, from 2018 to 2022, and involves analysing the returns and risk associated with the selected mutual funds. The research also investigates the factors that contribute to the performance of these funds, including asset allocation, portfolio composition, and market trends. The methodology includes both quantitative and qualitative analysis, with data collected from various sources such as fund fact sheets, annual reports, and financial websites. The findings of the study are expected to provide valuable insights for investors, fund managers, and other stakeholders in the Indian mutual fund industry and guide them about the prevalent mutual fund schemes which an investor can invest into.